Parents’ Concerns on Home Based Education Is it in the best interest of their child? - Julka, Anita (JOURNAL OF INDIAN EDUCATION, 2015)
Home Based Education (HBE), a programme was initiated by the Sarva Shiksha Abhiyan (SSA) for children with disabilities as a result of adopting a Zero rejection policy for all children. It became a legitimate right through the Right of Children to Free and Compulsory Education (Amendment) Act, 2012. The aim of this programme was to provide intensive specialised support to children with severe and profound disabilities at home so that they could be mainstreamed at a later stage, if possible. As a result of this Amendment, the number of children under the HBE programme have been increasing over the years. In the present study, 62 parents conducting such interventions in the States of Rajasthan, Uttarakhand, Goa and Karnataka were interviewed on issues like parents’ satisfaction with the programme, the problems faced by them in rearing up and educating their child with disabilities at home, the benefits they derived and the suggestions they can make regarding the improvement of the programme for better development of their child. Analysis revealed that although parents welcomed the interventions being provided and were also coping with the problems after consulting the resource teacher/ volunteer/caretakers, they felt that the training given to them or also to the resource provider was not adequate, the financial and other provisions were not sufficient, the frequency of visits of the resource provider needed to be increased and the child should get the opportunity of going to a school after building up the basic skills. The parents also had very low expectations from their child and showed a lot of pessimism in spite of the interventions.